Evaluación participativa de la sustentabilidad de sistemas de producción de cerdos en cama profunda en la comunidad de peña larga, Barinas - Venezuela (Agroindustria, Sociedad y Ambiente, 2018)
The participatory evaluation of the sustainability of the deep-bed pig breeding was carried out in the community of Peña Larga, located in the Alberto Arvelo Torrealba municipality, Barinas state; using environmental, social and economic sustainability indicators. The method with agroecological approach was used "Evaluation of Management Systems Incorporating Sustainability Indicators (MESMIS)", using information gathering techniques: participatory rural diagnosis, direct observation, interview and key informants and for the analysis of information the technique of multicriteria. Four units of family production of pigs in deep bed were characterized. The evaluation of the sustainability of the family production units of pigs in deep beds in the community of Peña Larga presents an average qualitative assessment, with a level of sustainability that is moderately sustainable with a sustainability index of 2.56. The limiting critical indicators of sustainability correspond to the economic and social dimension, with the influence of the attributes of productivity and self-management such as: crop yield, diversification of vegetable production, variation of prices of inputs, present organizations, dependence on external inputs and availability of local market for the sale of piglets, because they were classified as, potentially not sustainable and not sustainable, respectively. A collective proposal of strategic guidelines for community development aimed at improving the level of sustainability of the common critical indicators in the family production units was generated.
Keywords: Backyard breeding; MESMIS; Participatory Rural Diagnosis; Participatory Investigation; Sus scrofa